손목보조기가 키보드 타이핑작업 시 상지근육 피로도에 미치는 영향 - 김민; Mm Kim; 노정석; Jung Suk Roh; 신헌석; Heon Seock Cynn; 김장환; Jang Hwan Kim (Han'guk Chŏnmun Mulli Ch'iryo Hakhoe chi = Journal of the Korean Academy of University Trained Physical Therapists, 2008)
With the introduction of the video display terminal (VDT), the efficiency and productivity of work has improved. However, VDT syndrome is threatening the health of workers as a side effect of prolonged use of a VDT. Among various VDT syndromes, the musculoskeletal disorder, especially, the cumulative trauma disorder (CTD) is the common research topic related with upper extremities function. The aim of this study was to investigate the effect of the wrist-hand orthosis (WHO) on fatigue in middle deltoid, anterior deltoid, serratus anterior, and upper trapezius during one-hour computer keyboard typing. Twelve healthy subjects participated in this study. Surface electromyography was used to assess the localized muscle fatigue (LMF), and the LMF was calculated at 10 minutes, 20 minutes, 40 minutes, and 60 minutes in each muscle, with and without the WHO. Data were analyzed by paired t-test with a level of significance of .05. The results of this study are as follows: 1) At 10 minutes, the LMF decreased significantly with applied WHO in the middle deltoid, anterior deltoid, and upper trapezius (p=.001, p=.026, p=.019, respectively). 2) As the computer keyboard typing period increased, there were no significant LMF differences, except for the upper trapezius. Therefore, it can be concluded that the WHO can be applied to decrease the LMF for the initial 10 minute period in the middle deltoid, anterior deltoid, and upper trapezius' but that the long term effect of WHO in reducing the LMF was proven only in upper trapezius during continued computer keyboard typing.